PENGARUH BUDAYA ORGANISASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT SAMADISTA KARYA JAKARTA SELATAN - Yoga Surya Pratama; Andi Sopandi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Abstract. The purpose of this study is to determine the influence of organizational culture and work discipline on employee performance at PT Samadista Karya South Jakarta both partially and simultaneously. The method used is the Quantitative Associative method. The population in this study were all employees of PT Samadista Karya South Jakarta. The number of samples used was 82 respondents. The data analysis method used simple linear regression test, multiple linear regression, correlation coefficient, determination coefficient, partial t test and F test. The results of this study indicate that there is a positive and significant influence of organizational culture on employee performance at PT Samadista Karya South Jakarta, this can be proven from the simple linear regression equation Y = 25.645 + 0.379X1. The correlation value is 0.754 (strong relationship). The determination coefficient value is 56.9%. The t-value value is 10.268> t-table 1.990 with a significance of 0.000 <0.05. There is a positive and significant influence of work discipline on employee performance at PT Samadista Karya, South Jakarta, as evidenced by the simple linear regression equation Y = 25.013 + 0.395X2. The correlation value is 0.710 (strong relationship). The coefficient of determination is 50.4%. The calculated t value is 9.018 > t table 1.990 with a significance level of 0.000 < 0.05. Simultaneously, there is a positive and significant influence of organizational culture and work discipline on employee performance at PT Samadista Karya, South Jakarta, as evidenced by the multiple linear regression equation Y = 22.969 + 0.254X1 + 0.193X2. The correlation value is 0.792 (strong relationship). The coefficient of determination is 62.7%. The calculated F value is 66.268 > F table 3.11 with a significance level of 0.001 < 0.05.